Pengaruh Penerapan Sleep Hygiene dan Sleep Diary Terhadap Kualitas Tidur Anak Usia Sekolah di Kota Ambon - Joan Herly Herwawan; Reni Chairani; Syamsul Anwar (FORIKES, 2021)
Background: Sleep is one of the basic human needs, especially school age children because they are in a period of growth and development. However, several studies have shown a decrease in the quality of sleep experienced by children. The purpose of this study was to determine the effect of sleep hygiene and sleep diary implementation on the quality of sleep for school age children. Methods: This research was a quasi-experimental research by using pretest and posttest control group design. Purposive sampling technique was used with 80 respondents of school-age children who were divided non randomly into two groups using 2 Lameshow mean difference test formula. Instrument used to measure the sleep quality was the PSQI questionnaire. Results: The results of the analysis using the Wilcoxon test showed that there was a significant difference in the quality of sleep of children before and after the implementation of the intervention, with p-value of 0.000. Analysis using the General Linear Model Repeated Measure (GLM-RM) test showed that there was an effect of the application of the intervention on sleep quality with p-value of 0.000. Conclusion: The effect of sleep hygiene application and the use of sleep diaries could be used/applied as nursing interventions to improve the school-age children sleep quality. Keywords: school-age children; sleep quality; sleep hygiene; sleep diary ABSTRAK Latar Belakang: Tidur merupakan salah satu kebutuhan dasar manusia, terkhususnya anak usia sekolah karena mereka dalam masa pertumbuhan dan perkembangan. Namun beberapa penelitian menunjukkan terjadinya penurunan kualitas tidur yang dialami oleh anak. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh penerapan sleep hygiene dan sleep diary terhadap kualitas tidur anak usia sekolah. Metode: Penelitian ini merupakan penelitian quasi-experimental dengan desain penelitian pretest dan posttest control group design, dengan teknik purposive sampling terhadap 80 responden anak usia sekolah yang dibagi dalam 2 kelompok secara non-random dengan menggunakan rumus uji beda 2 mean Lameshow. Instrumen penilaian kualitas tidur menggunakan kuesioner Pittsburgh Sleep Quality Index (PSQI). Hasil: Hasil analisis menggunakan uji Wilcoxon menunjukkan terdapat perbedaan yang bermakna kualitas tidur anak sebelum dan sesudah diterapkannya intervensi. dengan p value = 0,000. Analisis menggunakan uji General Linier Model Repeated Measure (GLM-RM) menunjukkan bahwa ada pengaruh penerapan intervensi terhadap kualitas tidur dengan p-value = 0,000. Kesimpulan: Pengaruh penerapan sleep hygiene dan penggunaan sleep diary dapat dijadikan sebagai intervensi keperawatan untuk meningkatkan kualitas tidur anak usia sekolah. Kata kunci: anak usia sekolah; kualitas tidur; sleep hygiene; sleep diary